Penguatan Kapasitas Masyarakat dalam Penerapan K3 Kelistrikan PLTS Berbasis Pelatihan dan Simulasi Lapangan - Joessianto Eko Putro; Sholikhah, Evi Nafiatus; Catur Rakhmat Handoko; Moh. Basuki Rahmat; Riko Satrya Fajar J.P. (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to analyze the effectiveness of training and simulation in improving community members’ understanding and implementation of occupational health and safety (OHS) practices in photovoltaic (PV) system installations. The program was conducted through four stages: preparation, feasibility assessment, implementation, and community outreach and training, with participant learning outcomes evaluated using pre-test and post-test assessments. The data were analyzed using descriptive quantitative methods by comparing pre-test and post-test results. The findings demonstrated a substantial improvement in participants’ understanding, as reflected by an increase in test scores from 30–70 in the pre-test to 75–95 in the post-test. The training and simulation activities were effective in enhancing participants’ knowledge, practical skills, and awareness of OHS practices related to PV system installations. Furthermore, the program improved the community’s capacity to operate and maintain PV systems safely and effectively. These findings suggest that OHS training and simulation can serve as a sustainable community capacity-building model to promote the safe utilization of renewable energy, reduce the risk of occupational accidents, and foster a stronger culture of occupational health and safety within the community.